2019
DOI: 10.3390/molecules24244519
|View full text |Cite
|
Sign up to set email alerts
|

Zinc(II) Terpyridine Complexes: Substituent Effect on Photoluminescence, Antiproliferative Activity, and DNA Interaction

Abstract: A series of ZnCl2 complexes (compounds 1–10) with 4′-(substituted-phenyl)-2,2′:6′,2′′-terpyridine that bears hydrogen (L1), p-methyl (L2), p-methoxy (L3), p-phenyl (L4), p-tolyl (L5), p-hydroxyl (L6), m-hydroxyl (L7), o-hydroxyl (L8), p-carboxyl (L9), or p-methylsulfonyl (L10) were prepared and then characterized by 1H NMR, electrospray mass-spectra (ESI-MS), IR, elemental analysis, and single crystal X-ray diffraction. In vitro cytotoxicity assay was used to monitor the antiproliferative activities against tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 81 publications
(94 reference statements)
1
32
0
Order By: Relevance
“…Notably, the antiproliferative activity of 1 and 2 is better than that of the other compounds towards the three cell lines and, when the para-substituent is the same, the activity of the iodide anion complexes is generally better than that of the bromide anion ones. Compared with that of zinc chloride complexes [ 34 ], the antiproliferative activity of these complexes is stronger. This activity of the bromide complexes follows the order of 1 > 3 > 5 and that of the iodide complexes is 2 > 4 > 6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the antiproliferative activity of 1 and 2 is better than that of the other compounds towards the three cell lines and, when the para-substituent is the same, the activity of the iodide anion complexes is generally better than that of the bromide anion ones. Compared with that of zinc chloride complexes [ 34 ], the antiproliferative activity of these complexes is stronger. This activity of the bromide complexes follows the order of 1 > 3 > 5 and that of the iodide complexes is 2 > 4 > 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the interaction between complexes and proteins plays a key role in the distribution and transport of small molecules into the biological system, which affects the concentration and overall efficacy of drug molecules [ 31 ]. In our previous studies, it has been found that zinc complexes have strong antitumor activity [ 22 , 23 , 32 , 33 , 34 ]. It is noteworthy that the antitumor properties of these complexes can be regulated by the substituents at their 4′-position.…”
Section: Introductionmentioning
confidence: 99%
“…In order to find out a possible correlation between the cytotoxic activity in vitro and the chemical features of the surveyed complexes, we have cumulated the most active reported species (43 out of 102, i.e., all the complexes which exhibit an antitumoral activity with IC 50 values ≤ 10 µM ( Table 13 against one or more cancer cell lines, reaching in some cases the nanomolar range. In detail, penta-coordinated terpyridine derivatives 14a – j , [ 141 ] 15a – h [ 136 ] and 16 [ 142 ] and hexacoordinate bis-terpyridine 17 exhibited very high activity towards a large panel of cancer cell lines, and in the case of 16 and 17 demonstrated also a good specificity for tumor cells. On the other hand, at least for 16 and 17 , the free ligand is highly active per se and metal coordination did not lead to any improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Extremely active penta-coordinated zinc complexes 14a – j [ 141 ] and 15a – h [ 136 ] ( Figure 9 ) have been obtained by using terpyridine derivatives as ligands.…”
Section: Terpyridine and Pyridine-based Systemsmentioning
confidence: 99%
“…Substituted terpyridines such as 4 0 -chloro-2,2 0 :6 0 ,2 00 -terpyridine continue to be recognized as useful chelating ligands for many transition-metal ions, including platinum(II) (Qin et al, 2019), copper(II) (Choroba et al, 2019), cadmium(II) (Li et al, 2020), and zinc(II) (Li et al, 2019). Metal complexes containing zinc(II) and substituted terpyridines as chelating ligand have been shown to have promising antitumor activity (Liang et al, 2019).…”
Section: Structure Descriptionmentioning
confidence: 99%